Unveiling Clickbait: Analyzing SPOK Structure Errors in News Headlines - Sofyaningrum, Rosita; Latifah, Tanti (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2024)
Clickbait has become a popular strategy for attracting readers' attention in the digital era, but it often disregards fundamental principles of clear and informative headline writing. This study aims to analyze errors in the Subject, Predicate, Object, and Adverbial (SPOK) structure of clickbait headlines frequently used by online media. The research focuses on identifying incompleteness or inaccuracies in SPOK elements within these headlines and their impact on readers’ comprehension and perception. Using a qualitative descriptive analysis method with a linguistic approach, the study examines data from news headlines on various digital media platforms. The findings reveal that many clickbait headlines exhibit incomplete SPOK structures, such as the absence of an object or predicate, leading to ambiguous or unclear information. These errors can diminish media credibility as readers feel deprived of relevant or in-depth information from the presented headlines. Furthermore, incomplete SPOK elements create a gap between the news content and readers’ expectations, disrupting the effectiveness of journalistic communication. This research underscores the importance of fostering more responsible journalistic practices, particularly in crafting news headlines. By improving the SPOK structure in clickbait, media outlets can enhance the quality of information delivered, strengthen readers' trust, and support media literacy in the digital era.